Peningkatan Kesadaran Masyarakat Tentang Urgensi Kegiatan Keagamaan Pada Desa Botolempangan Kecamatan Bontoa Kabupaten Maros - Darmawangsih; Amrul Ikhwan; Syamraeni; Andi Firta Nurwafiq Azizah; Andi Mutmainnah; Irfandi; Rindi Setiawati; Nur Rahmadani; Hania Sirajang; Intan Fitria Sani (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2022)
Real work lectures (KKN) can create new changes in the Botolempangan community, one of which is in the field of religion and social service, so that there will be changes resulting from the holding of the real work lectures (KKN). As with the real work lecture (KKN) conducted by Botolemngan Village, Bontoa District, Maros Regency, students as agents of change can make a real contribution and empower the community through this KKN program. In this case the aim is to find out how the role of real work lectures is as a form of developing religious values for the Bolempangan community. Developing religious values is supported by several factors, one of which is the Community Service Program (KKN), which has a very influential role in society. This type of research is field research using the ABCD Asset Based Community Development program approach/method with the initial steps of conducting surveys, observations, direct interviews with Botolempangang village officials. The object is the Botolempangan village community. In this study it is known that the role of KKN in religious development for the community produces a positive role through programs that have been implemented by students.